Differences in perception of responsiveness between BPJS and non-BPJS patients - Nurmulia Wunaini, Ngkolu; Hadawiyah, Radiatul; Pratiwi, Reski Dewi (Community Research of Epidemiology (CORE), 2023)
Responsiveness is a person's ability to help and provide fast and appropriate service to every customer in the hospital. The background of this research is the decrease in the number of visits by Social Security Administration Agency (BPJS) Kesehatan patients and Non-BPJS Kesehatan patients at the Outpatient Installation at Tk.II Health Hospital 14.05.01 Pelamonia. The purpose of the study was to determine differences in the perception of responsiveness between BPJS Kesehatan patients and non-BPJS Kesehatan patients in the Outpatient Installation of Tk.II Hospital 14.05.01 Pelamonia.Research Methods This research is a quantitative descriptive cross-sectional approach. The sampling technique uses stratified random sampling. The number of samples in this study was 333, consisting of 317 BPJS Kesehatan patient respondents and 16 non-BPJS Kesehatan patient respondents. The data in this study were obtained by distributing questionnaires to patients. The results showed that there were significant differences between BPJS Kesehatan patients and non-BPJS Kesehatan patients in Prompt Attention (p = 0.000), Dignity (p = 0.000 Autonomy (p = 0.046), Basic amenities (p = 0.000), Choice Of Provider (p = 0.000), Dignity (p = 0.000), and Access to social support networks (p = 0.000), and there is no difference in perception between BPJS Kesehatan and non-BPJS Kesehatan patients for Comunnication (p = 0.548). Data analysis used the Mann-Whitney test. Non-BPJS Kesehatan patients in Outpatient Installations have a better perception of responsiveness than BPJS Kesehatan patients. It is hoped that the hospital will be able to improve the quality of service without having to differentiate between BPJS Kesehatan patients and non BPJS Kesehatan patients